2021
DOI: 10.1212/wnl.0000000000011274
|View full text |Cite
|
Sign up to set email alerts
|

Association of Peri-ictal Brainstem Posturing With Seizure Severity and Breathing Compromise in Patients With Generalized Convulsive Seizures

Abstract: ObjectiveTo analyze the association between peri-ictal brainstem posturing semiologies with post-ictal generalized electroencephalographic suppression (PGES) and breathing dysfunction in generalized convulsive seizures (GCS).MethodsProspective, multicenter analysis of GCS. Ictal brainstem semiology was classified as (1) decerebration: bilateral symmetric tonic arm extension, (2) decortication: bilateral symmetric tonic arm flexion only, (3) hemi-decerebration: unilateral tonic arm extension with contralateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 47 publications
2
25
2
Order By: Relevance
“…An increase in age correlates with an increase in tonic phase duration, which in turn correlates with an increase in PGES duration [17]. In adults, the presence of a tonic phase is associated with PGES, and the latter is remarkably longer with decerebrate posturing [26]. Compared to our cohort, adults seem to have more GTCS with symmetrical tonic arm extension [26,27].…”
Section: Pges and Gtcs Semiology In Children Are Relatedsupporting
confidence: 37%
See 1 more Smart Citation
“…An increase in age correlates with an increase in tonic phase duration, which in turn correlates with an increase in PGES duration [17]. In adults, the presence of a tonic phase is associated with PGES, and the latter is remarkably longer with decerebrate posturing [26]. Compared to our cohort, adults seem to have more GTCS with symmetrical tonic arm extension [26,27].…”
Section: Pges and Gtcs Semiology In Children Are Relatedsupporting
confidence: 37%
“…Seizure semiology is another potential marker of SUDEP. Studies in adults showed a positive association between GTCS semiology manifesting as decerebrate posturing, with symmetric bilateral arm tonic extension, and PGES duration [26,27]. Other semiologic characteristics, such as those related to the tonic phase of GTCS, may also be related [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in grouped analysis, we found some seizure features to worsen, namely duration of decerebrate posturing and ICA duration. Both decerebrate posturing duration and ICA duration are putative markers of seizure severity (39,40). Decerebrate posturing has been associated with PGES, a proposed SUDEP biomarker (40).…”
Section: Discussionmentioning
confidence: 99%
“…Both decerebrate posturing duration and ICA duration are putative markers of seizure severity (39,40). Decerebrate posturing has been associated with PGES, a proposed SUDEP biomarker (40). Similarly, prolonged ICA (>60 s) has been associated with severe hypoxemia (39).…”
Section: Discussionmentioning
confidence: 99%
“…In the highlighted study by Vilella and colleagues, the authors sought to indirectly relate presumed brainstem involvement during generalized seizures with clinical factors that might predispose to SUDEP in adult epilepsy patients. 2 Data were collected from 295 generalized seizures in 180 patients undergoing video-electroencephalogram (EEG) monitoring at multiple epilepsy monitoring units (EMUs), with approximately half of seizures captured during wakefulness and half during sleep. Approximately 16% of patients had a generalized epilepsy subtype, while most had presumed focal or multifocal onset, with temporal lobe localization being most common.…”
Section: Commentarymentioning
confidence: 99%